Budding Process During the Organogenesis of the Ventral Prostatic Lobe in Mongolian Gerbil - Azevedo Sanches, Bruno Domingos [UNESP]; Biancardi, Manoel Francisco; Alcantara Dos Santos, Fernanda Cristina; GoEs, Rejane Maira [UNESP]; Leite Vilamaior, PatriCia Simone [UNESP]; Taboga, SebastiaO Roberto [UNESP] (Wiley-Blackwell, 2014)
The prostate is a mammalian gland that shows a complex process of organogenesis. Here, a morphological study to characterize the organogenesis of the ventral prostate lobe in male gerbils was conducted. The urogenital sinus (UGS) was dissected out and processed for paraffin embedding. Histological sections were subjected to cytochemical, immunofluorescence, immunohistochemical, and three-dimensional reconstruction techniques. We found that the first ventral buds emerged from the ventral urethral epithelium between the days 20 and 21 of prenatal life, reaching the ventral mesenchymal pad and initiating the branching process on the first day of postnatal life. The buds presented a V-shaped elongation, suggesting that the smooth muscle layer (SML) plays an important role during budding events. Indeed, whereas the androgen receptor (AR) was preferentially found in the UGS mesenchyme (UGM), estrogen receptor alpha (ER alpha) was localized in both the UGM and in the emerging buds. This study characterized the morphological aspects of the budding process in a different rodent from rat and mice, serving as a new model for future studies on developmental biology of the prostate. (C) 2014 Wiley Periodicals, Inc.
Keywords: gerbil prostate; ventral mesenchymal pad; smooth muscle layer; androgen receptor; estrogen receptor alpha